2006
DOI: 10.1111/j.1365-2044.2006.04867.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the efficacy of HME filters at preventing contamination of breathing systems*

Abstract: SummaryBreathing system filters are intended to prevent cross-infection during anaesthesia. However, there is a lack of information on whether filters prevent contamination of the breathing system by the patient. We measured the contamination of 235 used filters of four different types obtained from operating theatres: two pleated hydrophobic (BB25M and BB22 ⁄ 15M, Pall Medical, Portsmouth, UK) used for adult patients and two electrostatic (355 ⁄ 5430 Hygroboy and 355 ⁄ 5427 Hygrobaby, Tyco Healthcare, Gosport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 7 publications
(10 reference statements)
0
15
1
2
Order By: Relevance
“…However, comparison of results from the HMEF 750 ⁄ S from main theatres in this study with results from the BB25 from the study by Rees et al [4] (carried out in the same theatres) showed a significant difference in contamination on the machine side between the two filters (Table 5): there was a greater incidence of excessive contamination (RLU > 50) with the HMEF 750 ⁄ S filter compared with the BB25. Cost was the factor that led to a change in the type of filter used.…”
Section: Discussioncontrasting
confidence: 42%
See 4 more Smart Citations
“…However, comparison of results from the HMEF 750 ⁄ S from main theatres in this study with results from the BB25 from the study by Rees et al [4] (carried out in the same theatres) showed a significant difference in contamination on the machine side between the two filters (Table 5): there was a greater incidence of excessive contamination (RLU > 50) with the HMEF 750 ⁄ S filter compared with the BB25. Cost was the factor that led to a change in the type of filter used.…”
Section: Discussioncontrasting
confidence: 42%
“…Other factors may include the type of airway device, depth of anaesthesia, position of the filter, smoking, medical history of asthma, current chest infection and patient position. These factors were not recorded in the study by Rees et al [4].…”
mentioning
confidence: 68%
See 3 more Smart Citations